Prenatal cannabinoid exposure and altered neurotransmission. (1st May 2019) - Pinky, Priyanka D.; Bloemer, Jenna; Smith, Warren D.; Moore, Timothy; Hong, Hao; Suppiramaniam, Vishnu; Reed, Miranda N.
Abstract: Marijuana is one of the most commonly used illicit drugs worldwide. In addition, use of synthetic cannabinoids is increasing, especially among adolescents and young adults. Although human studies have shown that the use of marijuana during pregnancy leads to adverse behavioral effects, such as deficiencies in attention and executive function in affected offspring, the rate of marijuana use among pregnant women is steadily increasing. Various aspects of human behavior including emotion, learning, and memory are dependent on complex interactions between multiple neurotransmitter systems that are especially vulnerable to alterations during the developmental period. Thus, exploration of neurotransmitter changes in response to prenatal cannabinoid exposure is crucial to develop an understanding of how homeostatic imbalance and various long-term neurobehavioral deficits manifest following the abuse of marijuana or other synthetic cannabinoids during pregnancy. Current literature confirms that vast alterations to neurotransmitter systems are present following prenatal cannabinoid exposure, and many of these alterations within the brain are region specific, time-dependent, and sexually dimorphic. In this review, we aim to provide a summary of observed changes to various neurotransmitter systems following cannabinoid exposure during pregnancy and to draw possible correlations to reported behavioral alterations in affected offspring. Highlights: Increased cannabinoid use during pregnancy and its impact on fetal health is a major issue of concern. Prenatal cannabinoid exposure has shown to modulate several neurotransmitter systems. Prenatal cannabinoid exposure has shown to adversely affect several behavioral outcomes in preclinical studies. The observed behavioral effects have often seemed to be sex dependent affecting the male population more. Future studies should be focused on investigating the downstream signaling mechanism for the altered neurotransmissions.